PENGARUH DEVIDEND PER SHARE DAN EARNING PER SHARE TERHADAP HARGA SAHAMPADA PERUSAHAAN GO PUBLIC DI BURSA EFEK INDONESIA - Datu, Christian V.; Maredesa, Djeini (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Rising share price means increases the value of a company. The company can hold and invest the revenues from on pay dividend shareholders, this can be harmful to shareholders that require that the information is the main thing that EPS need to be noted and made measure that better by investors in making a decision to invest, so that it will affect the demand for the corresponding company shares which in the end will affect the share price, where when investors consider EPS companies good enough and will produce a return in accordance with the risk that will be borne our griefs, then the demand for the shares of the company will increase, which means the company share price will also increase.Keywords : Dividends Per Share, Earning per Share (EPS), Share Price